Impacts of low sintering temperature on microstructure, atomic bonds, and dielectric constant of barium titanate (BaTiO3) prepared by co-precipitation technique. Issue 1 (1st March 2022) - Suherman, B; Nurosyid, F; Khairuddin; Sandi, D K; Irian, Y
Abstract: Barium Titanate (BaTiO3 or BT) is one of which the most attractive ferroelectric materials that have been widely studied. The fabrication process affects the properties of ferroelectric materials where increasing the sintering temperature is one of the ways to improve their performance. In this study, BT has been synthesized using the co-precipitation technique. The samples were sintered for 4 h with varying sintering temperatures of 700°C and 800°C. The purpose of this study was to investigate the effects of variation of sintering temperatures on the microstructure, dielectric constant, and chemical bonds of BT. The micro structure observed by the X-Ray Diffraction (XRD) showed that the crystal size of the sample at 800°C was larger than the sample at 700°C. Furthermore, the Fourier Transform Infrared (FTIR) analysis revealed that increasing the sintering temperature decreased the intensity of the impurities' peaks of C-H and C=O atomic bonds in the BT structure. The impurity that appear is the carbonate phase which does not decompose during the formation of BT. Moreover, based on the Resistance Capacitance Inductance (RCL Meter) examination, increasing the sintering temperatures could enhance the dielectric constant of the BT samples from 65 to 162. Thus, it can be inferred, that the increase in the sintering temperature could improve the crystal structure and decrease the impurities phases of the BT materials so that further could enhance the dielectric constant.